MiADMSA abrogates sodium tungstate-induced oxidative stress in rats. (2nd November 2022) - Sachdeva, Sherry; Sharma, Ankita; Flora, S. J. S.
Abstract: Tungsten (W) and its compounds have emerged as a relatively new area of environmental health concern in the last decade. Tungsten is environmentally benign due to its increasing use in armour-piercing munitions and as a replacement for lead in other ammunition. It has also been identified in various hazardous waste sites and therefore been proposed for inclusion in the Environmental Protection Agency National Priorities List. The major objective of this study was to evaluate the therapeutic efficacy of orally administered monoisoamyl 2, 3-dimercaptosuccinic acid (MiADMSA) against tungstate induced oxidative injury in blood, liver and kidneys of male Wistar rats. MiADMSA, a thiol chelator has gained wide recognition recently as a future chelating drug of choice specifically for arsenic and was chosen for this study as tungstate ions too have an affinity toward the –SH group thus, being less bioavailable in the body. We determined the effects of MiADMSA (50 mg/kg, p.o.) against sodium tungstate (500 ppm in drinking water, daily for 28 days) induced biochemical changes indicative of oxidative stress in blood, and other soft tissues of of male Wistar rats. Tungsten exposure led to an increased levels of Reactive Oxygen Species (ROS) in liver, kidney, spleen and blood accompanied also by an increase in TBARS levels. The GSH: GSSG ratio also showed a decrease on sodium tungstate intoxication. Treatment with MiADMSA restored most of the sodium tungstate-induced alterations in the biomarkers suggestive of oxidative stress. These preliminary results led us to conclude that sub-acute exposure to tungstate-induced oxidative stress could be effectively reduced by the administration of MiADMSA and thus might be a promising antidote for studying in detail its efficacy in reducing body tungstate burden and its excretion post tungstate exposure.